Dehydrin Expression and Drought Tolerance in Seven Wheat Cultivars - Lopez, Cesar G.; Banowetz, Gary M.; Peterson, C. James; Kronstad, Warren E. (Crop science, 2003)
The winter wheat (Triticum aestivum L.) producing region of the U.S. Pacific Northwest (PNW) is subject to periods of water deficit during sowing and grain filling. Improving the genetic adaptation of wheat to drought stress represents one of the main objectives of regional breeding programs. One biochemical response to dehydrative stress is the accumulation of a family of proteins called dehydrins, which are believed to protect membranes and macromolecules against denaturation. Although previous studies demonstrated the accumulation of dehydrins in drought-stressed wheat, little was known about the relation of dehydrin expression to acquisition of drought tolerance in specific varieties adapted to the PNW. We characterized dehydrin accumulation during the exposure of seven cultivars (`Connie', `Gene', `TAM105', `Rod', `Hiller', `Rhode', and `Stephens') to progressive drought stress in four separate experiments. The objective was to identify differences in the nature or timing of dehydrin expression in these cultivars and to learn whether dehydrin expression was associated with the acquisition of stress tolerance during seedling development. Expression of a 24-kDa dehydrin was observed in Connie, TAM105, and Gene after 4 d of stress and at subsequent sampling dates while no dehydrins were detected in nonstress control plants. Dehydrin expression was significantly delayed in the remaining cultivars. The presence of this dehydrin was related to acquisition of drought tolerance characterized by a greater maintenance of shoot dry matter production in Connie, TAM105, and Gene. Although the role of these proteins remains unknown, their association with stress tolerance suggests that dehydrins might be used to improve the adaptation to drought.